2021
DOI: 10.1016/j.rmed.2021.106665
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life profiles, trajectories, persistent symptoms and pulmonary function one year after ICU discharge in invasively ventilated COVID-19 patients, a prospective follow-up study

Abstract: Background: Health-related quality of life (HRQoL) impairment is often reported among COVID-19 ICU survivors, and little is known about their long-term outcomes. We evaluated the HRQoL trajectories between 3 months and 1 year after ICU discharge, the factors influencing these trajectories and the presence of clusters of HRQoL profiles in a population of COVID-19 patients who underwent invasive mechanical ventilation (IMV). Moreover, pathophysiological correlations of residual dyspnea were tested. Methods: We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 41 publications
11
89
3
1
Order By: Relevance
“…Three studies [25,34,35] showed a higher risk of long-term symptoms in severe/critical patients than non-severe patients in terms of the acute infection status, one study [36] found such association only for muscle fatigue but not for other symptoms, and another study [32] did not detect the association. In addition, one study [28] reported higher prevalence of long-term symptoms in hospitalised patients than non-hospitalised patients, and another study [24] found a positive association between duration of invasive mechanical ventilation and post-COVID dyspnoea at one-year follow-up.…”
Section: Evidence Of Risk Factors For One-year Post-covid Symptomsmentioning
confidence: 99%
“…Three studies [25,34,35] showed a higher risk of long-term symptoms in severe/critical patients than non-severe patients in terms of the acute infection status, one study [36] found such association only for muscle fatigue but not for other symptoms, and another study [32] did not detect the association. In addition, one study [28] reported higher prevalence of long-term symptoms in hospitalised patients than non-hospitalised patients, and another study [24] found a positive association between duration of invasive mechanical ventilation and post-COVID dyspnoea at one-year follow-up.…”
Section: Evidence Of Risk Factors For One-year Post-covid Symptomsmentioning
confidence: 99%
“…Some of them with larger samples, but with a smaller number of patients requiring invasive mechanical ventilation 6 , 7 , 21 . Only two studies 17 , 19 have assessed the three PICS domains focused on ventilated patients: the first one 17 assessed a cohort of 47 patients 6 months after hospital discharge, and the second one 19 analyzed a cohort of 178 patients at 3 and 12 months after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, follow-up consultations in that study 16 were via telematics at 1 month after hospital discharge. Gamberini et al 19 found that most of the patients reported persistent symptoms 1 year after ICU discharge, with dyspnea (58%) being the most frequent symptom. Heesakers et al 21 , also 1 year after ICU treatment, reported physical symptoms in 74% (weakness 38.9%), mental symptoms in 26% and cognitive symptoms in 16% of the patients, of whom 81% underwent mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations